PENERAPAN MIDTRANS PAYMENT PADA OFFICIAL SITE ASOSIASI PERGURUAN TINGGI SWASTA INDONESIA - Abas Sunarya; Andri Cahyo Purnomo; Muhamad Iqbal Wahib (UNIVERSITAS RAHARJA, 2019)
Association of Indonesian private universities an association representing the aspirations of more than three thousand private universities in Indonesia by committing to develop programs to advance private universities. Although APTISI focuses on activities to promote nationaleducation but APTISI official site utilization has been felt to be less than optimal in supporting APTISI activities. Therefore, the purpose of this research is to optimize a registration process by accessing APTISI official site that has been facilitated by online form and payment midtransto perform member funding transactions which can be done where and anytime as long as connected to internet without limited space and time , so registrants can perform easily and quickly. In this study the authors use several methods of analysis, consisting of SWOT, elicitation, Flowchart, UML, and Hipo. Results obtained from the implementation of this APTISI registration system can be used without the need to login email first, the registrant only needs to complete the stages it will get email notification data after making funding transactions and submit form update data of registrant members will get a confirmation of successful registration and get official email APTISI.